Confidentiality and help-seeking behavior for adolescents mental health problems - Olivari, Cecilia; Méndez-Bustos, Pablo; Núñez, Rodrigo; Sepúlveda-Ramírez, Ignacia (Acta Bioethica, 2022)
Prevention and early detection of mental health problems in the adolescent population is essential to reduce the possibility of developing more serious disorders. Likewise, seeking help for these problems and timely access to mental health care in this group is necessary. However, it has been found that adolescents tend not to seek professional help when they present symptoms of emotional disorders and, when they do seek help, they do so from informal sources. Various barriers, at the individual, structural, social, and health professional-patient relationship levels, can hinder help-seeking behavior in adolescents. Among these is young people’s concern about confidentiality. This article presents and analyzes evidence on the role of confidentiality in help-seeking behavior for mental health problems in adolescents, presenting an analysis from a bioethical perspective and pointing out some of its implications in the approach to youth mental health services.